Exposure to, understanding of and interest in interventional radiology among Pakistani medical students: a cross-sectional study - Chattha, Muneeb; Tahir, Muhammad Junaid; Zia, Ahmad; Chattha, Maha; Tariq, Waleed; Masood, Muhammad Faiq; Sani, Salman; Yousaf, Zohaib; Eljack, Mohammed Mahmmoud Fadelallah; Asghar, Muhammad Sohaib (Frontiers in Medicine, 2023)
Background Medical students need more awareness regarding minimally invasive image-guided procedures carried out by interventional radiological approach. This study analyzed the knowledge and attitudes of medical students regarding interventional radiology (IR) and the factors influencing their decision to choose IR as a specialty in the future. Methods A cross-sectional, web-based study was conducted among medical students across Pakistan. The data were collected from October 14, 2021, to November 14, 2021. The questionnaire included demographic variables, exposure, interest, and self-reported knowledge of IR, interventions, instruments utilized in IR, and the responsibilities of the interventional radiologist. Variables affecting the possible choice of IR as a future career were analyzed using logistic regression analysis. Results The median age was 22 years, with a male predominance. 65.5% exhibited an interest in radiology, and 20.2% in IR. The majority, 83.5%, perceived IR. As having good to adequate prospects. Male participants preferred IR more as compared to females. Participants willing to attend IR rotation and had an excellent view of IR as a specialty had higher propensity towards IR as a future career than their counterparts. The majority opted for IR as a better-paying job with lots of intellectual stimulation and career flexibility. Conclusion IR is a demanding specialty with rigorous routines but reasonable monetary compensation. Lack of infrastructure and low numbers of trained specialists limit medical students’ exposure to IR in developing health economies like Pakistan. Clinical rotations in IR departments would help raise awareness about the field and bridging this gap.